Порівняльний аналіз способів руху за довжиною кроку при вимірюванні розмірів циліндричних деталей - Скицюк, В.І.; Діордіца, І.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The article is devoted questions, to related to geometrical exactness of making of details of
cylindricity on lathes with the systems of CNC. Possibility of receipt of high-fidelity geometrical
forms of cylindrical kind is probed by the complex adaptive system at metal-workingness.